2013
DOI: 10.2478/v10298-012-0085-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nacl Priming on Emergence, Growth and Yield of Fenugreek Under Saline Conditions

Abstract: Salinity is considered as a major abiotic stress affecting crop production in arid and semi-arid regions in the world. Poor germination and decrease of seedling growth are major results of poor crop establishment and failure. Many research studies have shown that seed priming is an efficient method for increasing plant growth and yield in saline condition. For this reason, this experiment was conducted to evaluate the effects of NaCl priming on the emergence and seedling growth of Tunisian fenugreek (Trigonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
7
11
0
Order By: Relevance
“…This is probably due to the reaction of salinity, which reduces the contribution of phytohormones in the biosynthesis (Cuartero et al, 2006). These results are in accordance with Ahmet et al, (2009) and Soughir et al, (2013 …”
Section: Shoot Dry Weight (Mg)supporting
confidence: 83%
See 1 more Smart Citation
“…This is probably due to the reaction of salinity, which reduces the contribution of phytohormones in the biosynthesis (Cuartero et al, 2006). These results are in accordance with Ahmet et al, (2009) and Soughir et al, (2013 …”
Section: Shoot Dry Weight (Mg)supporting
confidence: 83%
“…In the present study a reduction in root dry weight was recorded in stressed conditions in all the genotypes. Present investigation is in confirmation with Ahmet et al, (2009) and Soughir et al, (2013). Root dry weight depends on the germination percent and root length, low water uptake and restricted metabolic activities were given to decrease in the root dry weight.…”
Section: Root Dry Weight (Mg)supporting
confidence: 79%
“…It was effective in alleviating the effect of salt stress on wheat plants through altering the levels of different plant phytohormones (Iqbal et al, 2006). Generally, primed seeds germinate faster and more uniformly than unprimed seeds of the same lot (Soughir et al, 2013;Elouaer and Hannachi, 2012). The difference between primed and control seeds are greater in arid and semi-arid conditions when there are more exposure to difficult environmental conditions such as salinity or water deficit.…”
Section: Introductionmentioning
confidence: 92%
“…Also, Khan et al (2009) observed that NaCl priming of seeds improved seedling vigor of pepper under salt stress conditions. Similarly, Soughir et al (2013) demonstrated that seed priming could be used successfully to ameliorate the emergence of fenugreek plants cultivated in pots under salt stress. So, the optimization of priming technique is important to determinate the optimal soaking duration and the optimal concentration of priming agent.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment increased the leaf area index. Soughir et al (2013) reported that leaf area index plants derived from primed seeds were higher compared with non-primed seeds.…”
Section: Leaf Area Indexmentioning
confidence: 99%